EXPOSURE OF RAW-264.7 MACROPHAGE CELL LINE TO WATER-SOLUBLE EXTRACT OF CHEDDAR CHEESE: ASSESSMENT OF ANTIOXIDANT ACTIVITY - S. Rafiq; N. Huma; I. Pasha; N. Gulzar; M. Shahid; H. Xiao (Journal of Animal and Plant Sciences, 2017)
Oxidative stress is the most critical factor implicated in various degenerative ailments. The present study was designed to evaluate the in vitro radical scavenging potential of water-soluble peptides (WSPs) extract derived from buffalo and cow milk cheddar cheeses during ripening. Moreover, the protective role of WSPs extract on cell viability and production of reactive oxygen species (ROS) in RAW-264.7 macrophages (Lipopolysaccharide- stimulated) cell line was also assessed. The WSPs extracts were potent scavenger of DPPH radical and activity increased progressively with cheese ripening period. Comparatively, highest activity was noticed in the peptide extract obtained from buffalo milk cheddar cheese. The intracellular ROS production in RAW-264.7 macrophages decreased signiﬁcantly (P<0.05) upon treatment with WSPs extract. However, the WSPs fraction collected at 150th day of ripening showed maximum reduction in ROS generation. Additionally, dose-dependent response of WSPs extract was noticed for antioxidant activity. The promising antioxidant potential of cheddar cheese can offer a perspective to reduce the risk of disorders associated with oxidative damage.
Keywords: Cheddar cheese; Peptides; Antioxidant; Macrophages